Valuing environmental changes - Mäler, Karl-Göran; Vincent, Jeffrey R. (Handbooks in economics, 2005)
Much applied environmental economics is concerned with the valuation of changes in environmental quality. Obtaining reliable valuation estimates requires attention to theoretical and econometric issues that are often quite subtle. Volume 2 of the Handbook of Environmental Economics presents both the theory and the practice of environmental valuation. It synthesizes the vast literature that has accumulated since the publication of the Handbook of Natural Resource and Energy Economics two decades ago. It includes chapters on individual valuation methods written by researchers responsible for.